Announcement effect of earnings surprises & dividend surprise on abnormal returns in the Singapore stock market. - Tan, Jane. (2008)
This report uses regression and time-event studies to analyse the effect of companies' announcements of earnings surprise on their stock prices. 81 Singapore Stock Exchange companies were used in this study.